Manejo comunicacional de las federaciones ecuatorianas deportivas - Padilla Bustamante, Geomira Elizabeth (2020)
The present study seeks to identify communication strategies in social networks for the effective dissemination of the activities carried out by the Ecuadorian Federation of Olympic Shooting. For this, a descriptive, non-experimental field-type methodology was used, with a quantitative approach, for which a survey is applied to a sample of 12 athletes from the Ecuadorian Federation of Olympic Shooting. According to the results, the communicational means by which the activities of the Ecuadorian Federation of Olympic Shooting can be disseminated are social networks, since these are used more frequently by the inhabitants in their daily lives. It is evident that the Ecuadorian Federation of Olympic Shooting has in its possession an account created on Facebook; however since its creation to date only 5 publications have been made. Being essential that this institution changes its communication image……………